Standardized astragalus extract for attenuation of the immunosuppression induced by strenuous physical exercise: randomized controlled trial - Ewa Latour; Jaroslaw Arlet; Emilia E. Latour; Artur Juszkiewicz; Karolina Łuczkowska; Anita Marcinkiewicz; Piotr Basta; Jerzy Trzeciak; Bogusław Machaliński; Anna Skarpańska-Stejnborn (Journal of the International Society of Sports Nutrition, 2021)
Background This paper aimed to verify how a supplementation of rower’s diet with Astragalus Membranaceus Root (AMR) modulated their immune system response to maximal physical exertion. Methods The double-blind study included 18 members of the Polish Rowing Team assigned to the supplemented group (n = 10), and the placebo group (n = 8). The participants performed a 2000 m test on a rowing ergometer at the beginning and at the end of the six-week of intensive training camp during which the supplemented group received 500 mg of AMR. Blood samples were obtained prior to, 1 min after completing, and 24 h after the exertion test. The levels of interleukin 2 (IL2), interleukin 4 (IL4), interleukin 10 (IL10), interferon ɤ (IFN-ɣ), and lactic acid were determined. Subpopulations of T regulatory lymphocytes [CD4+/CD25+/CD127−] (Treg), cytotoxic lymphocytes [CD8+/TCRαβ+] (CTL), natural killer cells [CD3−/CD16+/CD56+] (NK), and TCRδγ-positive cells (Tδγ) were determined with flow cytometry. Results After the camp, the initial NK and Treg levels sustained at the baseline, while Tδγ counts increased relative to the levels in the placebo group. In the supplemented subgroup, a decrease in IL2 level in reaction to maximal exertion clearly deepened while the change in IL-2/IL-10 level induced by the recovery after this exertion clearly increased, relative to the changes in the placebo group. Conclusions AMR restored the immunological balance in strenuously trained athlets through a stabilization of NK and Treg cells with a positive trend in Tδγ towards Th1 response during restitution by cytokine IL2 modulation.